The Hong Kong Influenza Virus: Treats to the Portrait after 50 Years and the Future Influenza Pandemic - E. P. Kharchenko (Эпидемиология и вакцинопрофилактика, 2020)
Relevance. Of the different subtypes, H3N2 influenza virus subtype has the highest variability and pathogenicity, often dominates in epidemiological seasons and induces high mortality exceeding its rate in pandemic. Aim is to identify some features of H3N2 molecular characteristics which could determine its high variability and domination over other subtypes in epidemiological seasons and discuss possible nature of the future influenza pandemic.Materials and method. For the computer analysis, the database of the hemagglutinin (HA) and nucleoprotein primary structures of the H3N2, H1N1, В\Yamagata and В\Victoria strains isolated in the influenza epidemiological seasons 2009-2019 were used from the Internet. From the primary structure of their genes it were defined their translational codes. To trace the H3N2 subtype evolution in the last decade we compared the H3 dominant sequences of adjacent seasons to establish their changes.Results. It has been indicated that H3, in comparison with H1 and В\Yamagata and В\Victoria hemagglutinins, contains more cysteine and the H3N2 strain very similar to the Hong Kong influenza virus continues to circulate in birds.The H3 gene translation code contains the least number of prohibitions. During last decade the H3 dominant sequence evolves faster than H1 one. The nucleoprotein of H3N2 strains is characterized by more content of lysine and less content of arginine.Conclusion: H3N2, H1N1, В\Yamagata and В\Victoria strains one may conclude that least of all the nature restricts H3N2 to evolve and adapt to new hosts. It is likely that the following influenza pandemic will be generated by H1N1 subtype but H3N2 one and also be more mild than the 2019 pandemic.